(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study of the features of German dialogic speech is in line with current trends in modern linguistic research. Recently, linguists have moved from studying language as a formal system to considering “language in action,” that is, in speech. In dialogical speech, the emotional function occupies an important place. The content of this function is a set of linguistic means that convey the emotional and evaluative attitude of the speaker to the statement. The purpose of this article is to identify and analyze linguistic means that create emotional evaluation.